2018
DOI: 10.1186/s12866-018-1272-y
|View full text |Cite
|
Sign up to set email alerts
|

The gut bacteria across life stages in the synanthropic fly Chrysomya megacephala

Abstract: BackgroundGut bacteria are closely associated with host. Chrysomya megacephala, as a vector and resource insect, can transmit various pathogenic bacteria and consume manure to produce biofertilizer and larva biomass. However, the gut bacteria composition and abundance of C. megacephala remain unclear.ResultsIllumina MiSeq platform was used to compare composition of gut bacterial community in eggs, 1-day-old larvae, 5-day-old larvae, pupae, adult females and males by sequencing with variation in V4 region of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…The beta-diversity analysis in the gut microbiota from C. incertus clustered initial (eggs), intermediate (larva and pupa), and adult stages (mother, offsprings). Similar results were reported for the synanthropic fly, Chrysomya megacephala (Wang et al, 2018). These changes in the bacterial communities of the gut microbiota throughout the host life cycle might be due to different factors: a) dietary specialization of adult and larvae.…”
Section: Discussion the Predominance Of Bacterial Groups According Tosupporting
confidence: 82%
See 1 more Smart Citation
“…The beta-diversity analysis in the gut microbiota from C. incertus clustered initial (eggs), intermediate (larva and pupa), and adult stages (mother, offsprings). Similar results were reported for the synanthropic fly, Chrysomya megacephala (Wang et al, 2018). These changes in the bacterial communities of the gut microbiota throughout the host life cycle might be due to different factors: a) dietary specialization of adult and larvae.…”
Section: Discussion the Predominance Of Bacterial Groups According Tosupporting
confidence: 82%
“…There is limited knowledge in the dung beetle's bacterial microbiota, in particular on its diversity and composition during the insect life cycle. Differences in the gut bacterial communities associated with life stages have been reported for several insect species like bark beetles (Briones-Roblero et al, 2017) flies (Wang et al, 2018), beetles (Arias-Cordero et al, 2012), and lepidopteran (Chen et al, 2016). However, the only one report in dung beetles in the genus Euoniticellus determined that the taxonomic abundance profiles in the microbiota in larvae, male and female parents were grouped according to developmental stage (Shukla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The adults transfer the microbes by smearing feces on the egg shells after oviposition [37]. The few studies there have shown that dipteran eggs have a low density, but a high diversity of bacteria ( Figure 2) [100,101]. Some freshly hatched larvae consume the egg shell and thus inoculate their guts with these microbes [93].…”
Section: Variations In Gbcs During the Life Cyclementioning
confidence: 99%
“…At the same time, Ignatzschineria was more abundant in the fly larvae specimens than in the living substrates, similar to our findings, were I. indica prevailed in L. illustris immature stages. Other synanthropic species, such as the oriental latrine fly, Chrysomya megacephala (Fabricius, 1794) was used for the microbiome characterization during the developmental cycle 43 . During the respective study 43 , both Ignatzschineria and Wohlfahrtiimonas were identified from the insect samples, though, unlike other experiments, these genera were not encountered among the prevailing gut bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Other synanthropic species, such as the oriental latrine fly, Chrysomya megacephala (Fabricius, 1794) was used for the microbiome characterization during the developmental cycle 43 . During the respective study 43 , both Ignatzschineria and Wohlfahrtiimonas were identified from the insect samples, though, unlike other experiments, these genera were not encountered among the prevailing gut bacteria. Nevertheless, once again it is demonstrated that these bacteria are present in different Diptera species, which may recommend them as universal biomarkers for the insect colonization time.…”
Section: Discussionmentioning
confidence: 99%